If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(2t + 6) = 24 Reorder the terms: -6(6 + 2t) = 24 (6 * -6 + 2t * -6) = 24 (-36 + -12t) = 24 Solving -36 + -12t = 24 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -12t = 24 + 36 Combine like terms: -36 + 36 = 0 0 + -12t = 24 + 36 -12t = 24 + 36 Combine like terms: 24 + 36 = 60 -12t = 60 Divide each side by '-12'. t = -5 Simplifying t = -5
| 6(2a+4)= | | 3(-2x+6)+3=0 | | -8x+14+2x=-36 | | -9v+45=-7(v-7) | | 6x-8=-40 | | 9x+3+4x-5=180 | | 8y-64=56 | | lg(x^2+1)=1 | | 11x-5+7x+27=180 | | 6-2x=4x+54 | | -2(m-30)=0-6m | | 3/4x=11/24 | | 4(16.5)-8+5b+6=180 | | 1-7c=27 | | 9x^2+4y^2=50 | | 5x+12=x-24 | | 9x^2+4y^2=502 | | 180-360/x | | 5/6y=5 | | (u-9)8=32 | | 5x+3y-6z=16 | | 3y=5+2x | | 25/25= | | (q-4)4=20 | | 8x-7=x-70 | | 2(3x+1)=-5(2x-3) | | -4x-8=-4x+24 | | -116-6v=-17v+5 | | 3x-18=7x+25 | | -116-6v=-17+5 | | 8r-5q=k | | x^2+4y^2=3x+2y |